Pengaruh Intellectual Capital Disclosure, Keputusan Investasi, Struktur Modal, dan Kebijakan Dividen terhadap Nilai Perusahaan - Darmawan, Aulia; Purwohedi, Unggul; Sariwulan, Rd. Tuty (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
The purpose of this research is to see the effect of Intellectual Capital Disclosure, Investment Decisions, Capital Structure, and Dividend Policy on Firm Value. The population in this study are food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study used a purposive sampling method and obtained 17 sample companies. This study uses multiple linear regression analysis method which is processed using the IBM SPSS Statistics 26 application. The results of this study indicate that disclosure of intellectual capital has no effect on firm value. investment decisions have a positive effect on firm value. Capital structure has a negative effect on firm value. Dividend policy has a positive effect on firm value.